Algumas notas sobre os primórdios do vinho e da vinha no Mediterrâneo - Estevão, Florbela (Trabalhos de Antropologia e Etnologia, 2020)
A brief introduction to our knowledge of the role and importance of wine in the Mediterranean world, with particular reference to its beginnings.